2022
DOI: 10.1088/1741-2552/ac8c6c
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of individual muscle units in natural contractions measured in vivo using ultrafast ultrasound

Abstract: Objective: The study of human neuromechanical control at the motor unit (MU) level has predominantly focussed on electrical activity and force generation, whilst the link between these, i.e., the muscle deformation, has not been widely studied. To address this gap, we analysed the kinematics of muscle units in natural contractions. Approach: We combined high-density surface electromyography (HDsEMG) and ultrafast ultrasound (US) recordings, at 1000 frames per second, from the tibialis anterior muscle to measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…A potential solution may be expanding current sEMG decomposition algorithms 10,11 to include spatial dependence or sparsity in addition to the temporal deconvolution and validating it using an authentic simulation model 28 . Yet, all these approaches need to deal with the motion of non-MU-related structures that hides a large part of the movement caused by a MU in ultrasound images 12 . One potential solution could be to use the spatiotemporal clutter filtering approach to improve the sensitivity to detect microvascular networks or blood flows corrupted by significant tissue or probe motion artefacts 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential solution may be expanding current sEMG decomposition algorithms 10,11 to include spatial dependence or sparsity in addition to the temporal deconvolution and validating it using an authentic simulation model 28 . Yet, all these approaches need to deal with the motion of non-MU-related structures that hides a large part of the movement caused by a MU in ultrasound images 12 . One potential solution could be to use the spatiotemporal clutter filtering approach to improve the sensitivity to detect microvascular networks or blood flows corrupted by significant tissue or probe motion artefacts 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Although including the temporal convolutive approach in ultrasound decomposition is promising, Lubel et al (2022) found that the motion of non-MU-related structures hides a large part of the movement caused by a MU in ultrasound images 12 . This finding is in line with the motivation for “over-decomposing” with the ultrasound decomposition method 3 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recent innovations have enabled imaging and analysis of MUs using magnetic resonance imaging (MRI) (Birkbeck et al, 2020;Heskamp et al, 2021) and ultrafast ultrasound (UUS) (Deffieux et al, 2008;Grönlund et al, 2013;Lubel et al, 2022). These imaging techniques provide high-resolution spatiotemporal information regarding the kinematics of the muscle fibres that are part of a MU.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound imaging can detect individual MU activity during voluntary isometric contractions [7,916]. The principle of detecting MU activity is based on the depolarization of the MU fibres, resulting in subtle axial displacements.…”
Section: Introductionmentioning
confidence: 99%
“…Second, displacement velocity images are calculated based on the raw ultrasound (radio frequency) data [18]. Third, the activity of individual MUs is localized in the displacement velocity images through spike-triggered averaging (using neural discharges from EMG concurrently) [16] or using blind source separation (BSS) [7,915]. The BSS algorithm extracts spatiotemporal components, where a subset is MUs [14,19].…”
Section: Introductionmentioning
confidence: 99%